Endophytic Bacillus atrophaeus CHGP13 and salicylic acid inhibit blue mold of lemon by regulating defense enzymes - Maalik, Saba; Moosa, Anam; Zulfiqar, Faisal; Aslam, Muhammad Naveed; Mahmood, Tahir; Siddique, Kadambot H. M. (Frontiers in Microbiology, 2023)
Lemons (Citrus limon L.) are one of the most economically important and consumed fruits worldwide. The species is vulnerable to several post harvest decay pathogens, of which Penicillium italicum is the most damaging, causing blue mold. This study investigates the use of integrated management for blue mold of lemon using lipopeptides extracted from endophytic Bacillus strains and resistance inducers. Two resistance inducers—salicylic acid (SA) and benzoic acid (BA) were tested (2, 3, 4, and 5 mM) against the development of blue mold on lemon fruit. The 5 mM SA treatment produced the lowest disease incidence and lesion diameter of blue mold on lemon fruit. In an In vitro antagonism assay eighteen Bacillus strains were evaluated for their direct antifungal effect against P. italicum; CHGP13 and CHGP17 had the greatest pathogen inhibition. Lipopeptides (LPs) extracted from CHGP13 and CHGP17 also inhibited colony growth of P. italicum. We tested 5mM SA and the LPs extracted from CHGP13 as stand-alone and combined treatments against disease incidence and lesion diameter of blue mold on lemon fruit. SA+CHGP13+PI had the lowest disease incidence and lesion diameter of P. italicum on lemon fruit relative to the other treatments. Furthermore, the lemon fruit treated with SA+CHGP13+PI had the highest PPO, POD, and PAL activities. The post-harvest quality analysis of the lemon fruit (fruit firmness, total soluble solids, weight loss, titratable acidity, ascorbic acid content) revealed that the combined treatment (SA + CHGP13) had little effect on fruit quality compared to the healthy control. These findings indicate that Bacillus strains and resistance inducers can be used as components of integrated disease management for blue mold of lemon.